Related factors of psychotic symptoms in adolescent patients with depressive disorder - Hao Mingru; Liu Lewei; Zhao Xin; Shen Qingqing; Fan Haojie; Xia Lei; Geng Feng; Mo Daming; Liu Huanzhong (Sichuan jingshen weisheng)
BackgroundPatients demonstrating depressive disorder with psychotic symptoms often have increased risk of death and poor prognosis. A large amount of research has explored the factors influencing psychotic symptoms in adult patients with depressive disorder， but few has focused on adolescent patients.ObjectiveTo explore the influencing factors of psychotic symptoms in adolescent patients with depressive disorder， so as to provide references for early screening and intervention in clinic.MethodsA total of 96 adolescent patients who met the Diagnostic and Statistical Manual of Mental Disorders， fifth edition （DSM-5） for depressive disorder and were seen in the psychiatry departments of Chaohu Hospital of Anhui Medical University and The Fourth People's Hospital of Hefei from September 2022 to January 2023 were included. Another 56 healthy individuals from the health examination center of Chaohu Hospital of Anhui Medical University were concurrently recruited as control group. Patients were assigned into psychotic group （n=32） and non-psychotic group （n=64） according to the presence or absence of psychotic symptoms. Hamilton Depression Scale-24 item （HAMD-24）， Positive and Negative Syndrome Scale （PANSS）， Positive and Negative Suicide Ideation （PANSI） and Childhood Trauma Questionnaire-Short Form （CTQ-SF） were used for evaluation. Plasma brain-derived neurotrophic factor （BDNF） concentration was obtained using Meso Scale Discovery electrochemiluminescence assay. Pearson and Spearman correlation analysis were adopted to determine the correlation of PANSS positive symptom subscale score with plasma BDNF concentration and clinical characteristics of adolescent depression patients with psychotic symptoms. Binary Logistic regression analysis was used to identify the factors influencing the presence of psychotic symptoms in adolescent patients with depressive disorder， and multiple linear regression analysis was utilized to screen the factors affecting the severity of psychotic symptoms.ResultsThe plasma BDNF concentration of adolescent patients with depressive disorder was lower than that of control group （t=-3.080， P<0.01）.The plasma BDNF concentration of psychotic group was lower than that of non-psychotic group （t=2.418， P<0.05）， while the body mass index （BMI） PANSI scores， CTQ-SF scores and HAMD-24 total scores were all higher than those of non-psychotic group （t=-2.024， -2.530， -2.187， -4.977， P<0.05 or 0.01）. Correlation analysis showed that PANSS positive symptom subscale scores were negatively correlated with anxiety/somatization factor score and weight factor score in HAMD-24 of psychotic group （r=-0.438， -0.498， P<0.05 or 0.01）. Binary Logistic regression showed that BMI， plasma BDNF concentration， HAMD-24 total scores and cognitive dysfunction factor score were the influencing factors of psychotic symptoms in adolescent patients with depressive disorder. Multiple linear regression analysis demonstrated that weight factor scores （β=-0.349， P<0.05） and anxiety/somatization factor score （β=-0.433， P<0.05） in HAMD-24 were the factors influencing the severity of psychotic symptoms.ConclusionHigh BMI， low plasma BDNF concentration， severe depressive symptoms and cognitive dysfunction may be the risk factors of psychotic symptoms in adolescent patients with depressive disorder， furthermore， BMI and anxiety symptoms are found to be associated with the severity of psychotic symptoms. ［Funded by Scientific Research Fund Project of Anhui Institute of Translational Medicine （number， 2022zhyx-B01）； Central Finance Supported Provincial Key Clinical Specialty Construction Project of Anhui Province in 2019］